Physicochemical properties of ethanol with the addition of biodiesel for use in Otto cycle internal combustion engines: Results and revision. (July 2017) - Vanzela, Edson; Nadaleti, Willian Cézar; Bariccatti, Reinaldo Aparecido; Cremonez, Paulo André; de Rossi, Eduardo; Filho, Paulo Belli; Andreazza, Robson; Quadro, Maurizio Silveira; de Souza, Samuel Nelson
Abstract: The goal of this research is to evaluate the effect of adding different concentrations of biodiesel to ethanol, analyzing its heating value, viscosity, flash point and density. Eight different compositions were carried out (4 blends with soybean biodiesel and 4 with castor bean oil), by varying the percentage of biodiesel at 1%, 3%, 5% and 10% (m/m) hydrous ethanol. The highest heating value increase was achieved in the blend with 10% soybean biodiesel (+8.70%). The blend with 10% castor bean biodiesel showed a viscosity increase of 23.8% whereas blends with 5% castor bean oil and 10% soybean biodiesel presented a viscosity increase of 15%. The flash point for blends with 10% soybean and castor bean biodiesel increased by just over 1 °C, improving safety condition in the handling of the fuel. The density exceeded the specified limit of 1.42% for the blend with 10% castor bean oil. This parameter is dependent on the amount of water present in ethanol, which in this study achieved the maximum limit, thus making the density of the blends exceed the threshold.